Complexes of Nickel(II), Copper(II) and Zinc(II) Metal Ions with a Tetrabasic Octadentate Schiff-Base Derived from 3,3´ -Diamino-Benzidine and Salicylaldehyde - A. Mustafa, Ihsan; KH. Al-A Sa'ady, Basma; A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
The reaction between 3,3´-diaminobenzidine and salicylaldehyde in 1:4 molar ratio affords a novel tetrabasic octadentate Schiff base (H4L). Its reaction with Ni(OAc)2 or Zn(OAc)2 in 1:2 molar ratio leads to the formation of dinuclear complexes of the general formula [M2L] and the latter, in turn, reacts with the metal halide M´X2 (M´ = Co, Ni, Cu, X = Cl or Br) in 1 : 2 molar ratio to form tetranuclear complexes of the general formula [M2LM´2X4]. The coordination of the Schiff base in the dinuclear complexes seems to occur via N-azomethine followed by deprotonation of the OH groups, while the further coordination in the tetranuclear complexes seems to take place via the lone pair of electrons available on the oxygen atoms. The structural features of the chelates have been confirmed by elemental analytical data, IR, UV-Vis and magnetic measurement.